How Irrigation Affects Soil Erosion Estimates of RUSLE2 - Dabney, S.; Yoder, D. (Agrociencia Uruguay, 2015)
RUSLE2 is a robust and computationally efficient conservation planning tool that estimates soil, climate, and land management effects on sheet and rill erosion and sediment delivery from hillslopes, and also estimates the size distribution and clay enrichment of sediment delivered to the channel system. In the U.S.A., RUSLE2 is supported by extensive databases maintained by the USDA-Natural Resources Conservation Service. Examples are presented of how input climate, soil and management descriptions might be built outside the U.S.A. using data from Uruguay. In addition to average annual erosion and sediment delivery, recent enhancements give RUSLE2 the ability to predict a representative runoff event sequence for a particular location, soil, management, and user-specified return period that can be coupled with a channel erosion and routing model.